2009
DOI: 10.1002/bmb.20283
|View full text |Cite
|
Sign up to set email alerts
|

The use of contextual learning to teach biochemistry to dietetic students

Abstract: This article describes the use of contextualized and ''blended'' learning to teach biochemistry to dietetic students during the second year of their professional training in a 4-year undergraduate degree (Bachelor of Nutrition and Dietetics). Contextualized content was used to engage students and motivate them to learn biochemistry, which many perceived as a ''hard'' subject. Contextualized learning presented via problem solving exercises, case-studies, and by the use of virtual subjects in laboratory class in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
0
17
0
6
Order By: Relevance
“…This observation suggests that the time flexibility can provide different learning options, stimulating students' active involvement in the activities proposed, as emphasized by Sé et al [4]. Similarly, Macaulay et al [23] reported that the integration of a VLE for teaching biochemistry to students FIG. 1.…”
Section: Students' Perception Of the Vle Integration Into The Teachinmentioning
confidence: 74%
“…This observation suggests that the time flexibility can provide different learning options, stimulating students' active involvement in the activities proposed, as emphasized by Sé et al [4]. Similarly, Macaulay et al [23] reported that the integration of a VLE for teaching biochemistry to students FIG. 1.…”
Section: Students' Perception Of the Vle Integration Into The Teachinmentioning
confidence: 74%
“…6 Apabila modul guru dan siswa dipisah, pada modul guru ditambahkan RPP dan strategi pembelajaran sebelum kegiatan belajar dan rambu pengerjaan modul di akhir kegiatan belajar.…”
Section: Tabel 2 Perbaikan Pada Validasi Mediaunclassified
“…Portanto, os AVAs parecem ter sido mais utilizados para disponibilizar conteúdo textual e menos para explorar o potencial das TICs para a representação de informações visuais, sejam elas em imagens estáticas ou dinâ-micas em diferentes mídias, tal como relatado por outros autores 42,43 . Vários estudos relatam que esses recursos multimídia contribuem de forma efetiva para a aprendizagem de conceitos abstratos e de difícil visualização, bem como de processos que se desenvolvem ao longo do tempo, impossíveis de serem observados, acompanhados e controlados em situações reais 19,36,54 . Tais conceitos e processos são inerentes aos conhecimentos das ciências básicas e clínicas e, portanto, importantes para a educação médica 18,55 .…”
Section: Ekaterini Simões Goudouris Et Alunclassified